Bayesian evidence for both astrophysical and primordial black holes: mapping the GWTC-2 catalog to third-generation detectors. Issue 5 (3rd May 2021) - De Luca, V.; Franciolini, G.; Pani, P.; Riotto, A.
Abstract: We perform a hierarchical Bayesian analysis of the GWTC-2 catalog to investigate the mixed scenario in which the merger events are explained by black holes of both astrophysical and primordial origin. For the astrophysical scenario we adopt the phenomenological model used by the LIGO/Virgo collaboration and we include the correlation between different parameters inferred from data, the role of the spins in both the primordial and astrophysical scenarios, and the impact of accretion in the primordial scenario. Our best-fit mixed model has a strong statistical evidence relative to the single-population astrophysical model, thus supporting the coexistence of populations of black-hole mergers of two different origins. In particular, our results indicate that the astrophysical mergers account for roughly four times the number of primordial black hole events and predict that third-generation detectors, such as the Einstein Telescope and Cosmic Explorer, should detect up to hundreds of mergers from primordial black hole binaries at redshift z≳30.